2022
DOI: 10.53518/mjavl.1113511
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Clinical and Serum Biochemical Evaluation of Two Intramuscular Anaesthetic Combinations (Diazepam/Ketamine and Diazepam/Fentanyl/Ketamine) in Rabbits

Abstract: The clinical efficacy and safety of preanaesthetics and induction agents were examined and compared on the basis of clinical and serum biochemical indicators in rabbits. Eight apparently healthy rabbits (3.0-3.5kg) of either sex were arbitrarily allocated into two groups: Group DK (diazepam-ketamine) and Group DFK (diazepam-fentanyl- ketamine). Rabbits were received intramuscular diazepam (5mg/kg), fentanyl (0.02 mg/kg) and ketamine (35 mg/kg). Data on clinical parameters (rectal temperature, heart rate and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In comparison to fentanylketamine anesthesia, the current study demonstrated that xylazine-ketamine anesthesia produced a longer duration of anesthesia and a more seamless recovery. The outcomes of the xylazine-ketamine anesthesia were consistent with the previously published research on sheep [21] and chicks [22,23], as well as rabbits [24, 25,26].…”
Section: Resultssupporting
confidence: 88%
“…In comparison to fentanylketamine anesthesia, the current study demonstrated that xylazine-ketamine anesthesia produced a longer duration of anesthesia and a more seamless recovery. The outcomes of the xylazine-ketamine anesthesia were consistent with the previously published research on sheep [21] and chicks [22,23], as well as rabbits [24, 25,26].…”
Section: Resultssupporting
confidence: 88%
“…Ketamine and xylazine can be injected simultaneously in rats and mice, and this procedure is slightly different in rabbits (Table 1). First xylazine (5 mg/kg) injection is administered IM, and 10 minutes later ketamine (30 mg/kg) is administered IM in rabbits (12,13). Locally administered bupivacaine (0.25% solution) and lidocaine (1% solution) are local anesthetics and can be used for short procedures in the incision area in mice and rats.…”
Section: Injectable Anesthetics In Rodentsmentioning
confidence: 99%